The effectiveness of online collaborative learning towards programming skills among undergraduate students in learning programming - Yahya, Amal Hayati (Secholian Publication, 2023)
Programming skills are very crucial for the students who want to land their future career in software development field. Many methods are done to increase the programming skills among the students. Therefore, this research was conducted to study the effectiveness of online collaborative learning towards programming skills among undergraduate students in learning programming. A quantitative research design, a pre-experimental study of a one-group pre and post-test method is employed in this research. 30 undergraduate students who were taken programming course in a public institution in Pulau Pinang were selected by using the purposive sampling technique. Data were obtained by using pre and post assessment tests. Paired samples t-test was conducted to determine the effect of online collaborative learning on students’ programming skills. The results indicate a significant difference between programming score before the treatment (M=63.53; SD=19.83) and programming score after the treatment (M=92.43; SD=8.14); [t (29) = 11.38, p = .001]. In conclusion, this study revealed that an online collaborative learning is effective towards students’ programming skills among undergraduate students in programming course.